Peningkatan Kemampuan Bina Diri Dalam Menggosok Gigi Melalui Penerapan Analisis Tugas Pada Anak Tunagrahita Ringan Kelas III di SLB Kreasi Mandiri Manado - Duyo, Usman; Siwi, Femmy Debora; Sinedu, Anggita Anjalita (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out whether the application of task analysis can improve the self-development ability in brushing teeth in mildly mentally retarded children in class III at SLB Kreasi Mandiri Manado. The method used in this research is an experimental method with a single subject or Single Subject Research (SSR). The research design used was A1-B1-A2-B2 consisting of baseline-1, intervention-1, baseline-2 and intervention-2. The research subjects were class III mild retarded students at SLB Kreasi Mandiri Manado, namely EW subjects. Data collection was carried out by observation, interviews and documentation. Data analysis takes the form of analysis within conditions and analysis between conditions. The results of the research show that the application of task analysis can improve the self-development ability in brushing teeth in mildly mentally retarded children in class III at SLB Kreasi Mandiri Manado in terms of frequency in terms of frequency of self-development in brushing teeth. This is indicated by the data overlap of 20%. Based on the research results, it can be concluded that the application of task analysis can improve self-development in brushing teeth in mildly mentally retarded children in elementary class III SLB Kreasi Mandiri Manado.